Live Donor Liver Transplantation: A Valid Alternative for Critically Ill Patients Suffering From Acute Liver Failure. Issue 6 (19th March 2015) - Goldaracena, N.; Spetzler, V. N.; Marquez, M.; Selzner, N.; Cattral, M. S.; Greig, P. D.; Lilly, L.; McGilvray, I. D.; Levy, G. A.; Ghanekar, A.; Renner, E. L.; Grant, D. R.; et al.
<x xml:space="preserve">Abstract</x> We report the outcome of live donor liver transplantation (LDLT) for patients suffering from acute liver failure (ALF). From 2006 to 2013, all patients with ALF who received a LDLT (n = 7) at our institution were compared to all ALF patients receiving a deceased donor liver transplantation (DDLT = 26). Groups were comparable regarding pretransplant ICU stay (DDLT: 1 [0–7] vs. LDLT: 1 days [0–10]; p = 0.38), mechanical ventilation support (DDLT: 69% vs. LDLT: 57%; p = 0.66), inotropic drug requirement (DDLT: 27% vs. LDLT: 43%; p = 0.64) and dialysis (DDLT: 2 vs. LDLT: 0 patients; p = 1). Median evaluation time for live donors was 24 h (18–72 h). LDLT versus DDLT had similar incidence of overall postoperative complications (31% vs. 43%; p = 0.66). No difference was detected between LDLT and DDLT patients regarding 1‐ (DDLT: 92% vs. LDLT: 86%), 3‐ (DDLT: 92% vs. LDLT: 86%), and 5‐ (DDLT: 92% vs. LDLT: 86%) year graft and patient survival (p = 0.63). No severe donor complication (Dindo–Clavien ≥3 b) occurred after live liver donation. ALF is a severe disease with high mortality on liver transplant waiting lists worldwide. Therefore, LDLT is an attractive option since live donor work‐up can be expedited and liver transplantation can be performed within 24 h with excellent short‐ and long‐term outcomes.